Analisis Kelayakan Finansial dan Nilai Tambah Industri Terasi Di Desa Sumberjaya, Kecamatan Tempuran, Kabupaten Karawang - Deva Suryo Deva Suryo praja; Kuswarini Sulandjari; I Putu Eka Wijaya (Paspalum: Jurnal Ilmiah Pertanian, 2024)
The shrimp paste industry in Sumberjaya Village, Karawang Regency, is a processing industry made from fish and shrimp using fermentation and salting methods to produce shrimp paste. The sustainability of this industry is maintained through its business feasibility. The added value created is economically beneficial. This research aims to evaluate the financial feasibility of businesses and the added value of the shrimp paste industry. The method used is quantitative-descriptive. Sampling used the saturated sampling method in a total of 13 shrimp paste industries. Data collection was carried out through interviews with shrimp paste industry players who had milling machines and those who did not. The data was then analyzed using cost analysis, break-even point (BEP), R/C, and added value analysis using the Hayami. method. The results of the research show that producers who have milling machines spend an average of Rp1,680,161/month, income Rp8.060.000, income Rp6.417.296, R/C ratio 4,9, BEP price Rp13.302, BEP production 2kg. Shrimp paste producers who do not have a grinding machine on average per month spend Rp895.497, income Rp3.412.500, revenue Rp2.517.003, R/C ratio 3.81, BEP price Rp17.076, BEP production 0.87kg. Producers who use milling machines are able to obtain an added value of Rp49.480,33 per kilogram, or 89%; producers without milling machines obtain an added value of Rp48.351.60 per kilogram, or the equivalent of 86%; thus, the shrimp paste industry is profitable and worth trying.